Communicating Concepts in an Interdisciplinary Project: Four Models of a Lake Described in the DELTA Language - Møller-Pedersen, Birger (DAIMI Report Series, 1977)
This report is the first part of an English version of a Master's Thesis. In this thesis the DELTA language was used in the description of four different models of the same system, the experiences with the use was reported and an extension of DELTA by a context concept was proposed. This report covers the use of the DELTA language. A forthcoming report (DAIMI PB-83) will deal with the proposed extension by a context concept. This report is also referred to as DELTA Project Report No. 7.